Critical Thinking Ability in terms of Adversity Quotient on DAPIC Problem Solving Learning - Wulandari, Ika Putri; Rochmad, Rochmad; Sugianto, Sugianto (Unnes Journal of Mathematics Education Research, 2020)
The research aims to explain and analyze students' critical thinking ability in DAPIC (Define, Asses, Plan, Implement, and Communicate) Problem Solving learning in terms of Adversity Quotient. The research method is descriptive qualitative research. Sampling technique used purposive sampling method and based on three categories of Adversity Quotient, namely quitter, camper, and climber. The research subjects were nine students of class VIII B State Junior High School 3 Sindang Indramayu. Data collection used five questions of critical thinking ability, 30 items of adversity quotient questionnaire, and triangulation to check data validity. The results showed (1) critical thinking ability of the quitter students had been completed by four indicators; (2) critical thinking ability of the camper students has completed five indicators but does not solve them correctly and; (3) critical thinking ability of the climber students has completed five indicators correctly.